PENGEMBANGAN KREATIVITAS ANAK USIA DINI DALAM KELUARGA - Handayani, Peny Husna; Gandamana, Apiek; Farihah, Farihah (Universitas Negeri Medan, 2017)
Early age is an important time for the development of one's creativity. Creativity is necessary in the development of children because it will affect the work of the right brain and left brain. Creativity is a necessity in the present and also in the future. Creativity is needed to pick up the century of competition because developing individual creativity can produce innovative work or something new that is needed by the times. Family is the first and foremost teacher in child development. In educating children to grow into a creative person parents should accompany children in the growth period.